Research on the Role of Bac Ai Pumped Storage Hydropower in the Operation of Vietnam’s Power System in 2030 with a High Proportion of Renewable Energy - Giap, Luong Ngoc; Le, Ngo Phuong; Khanh, Nguyen Binh; Trung, Bui Tien; Tuong An, Truong Nguyen; Vinh, Tran The; Tu, Le Tat (Engineering, Technology & Applied Science Research, 2024)
Research on solutions to improve the regulation capacity of power systems is essential and urgent in the context of renewable energy sources being highly variable and constituting a significant proportion of Vietnam’s power system by 2030. Pumped storage hydropower plants serve as an excellent energy reserve and are widely used to provide peak energy demands for daily and nightly loads. In Vietnam, the Bac Ai hydropower storage project, currently under construction, is the first of its kind and is expected to play a significant role as a large-scale energy storage system. This comes at a time when renewable energy sources are growing rapidly, with many large-scale solar and wind power plants being invested and commissioned. This project will be crucial to addressing surplus and shortage issues in power system load, stabilizing the system, regulating frequency, and ensuring stable, safe, and reliable operation of the national power grid. However, to assess the necessity of this project within the Vietnamese power system, scientific evaluations are required regarding the impact of capacity scale, timing, and operational position of this project within the development scenarios of Vietnam’s power system. This study investigates an optimization problem for the operation of the Vietnamese power system, considering the characteristics of generation sources and transmission lines using the PyPSA software. The aim is to calculate and identify the role of the Bac Ai pumped storage hydropower plant in Ninh Thuan province in the 2030 scenario of Vietnam’s power system, which includes a high proportion of renewable energy sources.